Darkness ebook - Robards, Karen (2016)
New York Times bestselling author Karen Robards continues her penchant for "fantastic storytelling" ( RT Book Reviews ) with this heart-pumping and nail-biting tale of a brilliant ornithologist trapped on the remote Attu Island in Alaska, fighting for her life—and that of a handsome stranger—before they're swallowed up in darkness forever. Ornithologist Dr. Gina Solomon, PhD, can't believe her good fortune when she's picked as one of a small group of Stanford University scientists lucky enough to be allowed to conduct research on Attu Island, Alaska. But a dream come true soon turns into a nightmare when she witnesses the horrifying break-up of a small plane. As the pieces rain down around her into the frigid waters of the Bering Sea, Gina heads toward the crash site looking for survivors and discovers James "Cal" Callahan. But when the two realize the plane crash wasn't an accident—and that the individuals responsible are still on the island—will they escape before they're swallowed up in darkness forever? Set against the harsh wilderness of Alaska, Darkness is yet another of Robards's "scintillating romantic thrillers" ( Publishers Weekly ) featuring the well-paced suspense and twists that has made Robards an icon in the romance genre.